Peran Pendidikan Pancasila dalam Menangkal Krisis Identitas Nasional di Era Digital - Fariha Safrotul Haz; Meita Sulastri; Maria Gibtia; Rika Amelia; Iwan Ridwan Paturochman (Publikasi Inspirasi Indonesia, 2025)
Young people's perceptions of national identity have changed significantly as a result of digital transformation. Identity crises and the erosion of nationalism are major issues that have emerged due to exposure to global culture and the overwhelming flow of digital information. Using a qualitative approach and literature review methodology, this article critically examines the strategic role of Pancasila Education in strengthening national identity in the digital age. The findings show that barriers to internalizing Pancasila values include traditional teaching methods, the absence of digital literacy integration, and a lack of relevant context in the material. Therefore, innovations in technology-based learning, flexible curricula, and teacher preparation focused on digital pedagogy are necessary. In addition, cross-sectoral collaboration between educational institutions, the government, and the creative sector is essential to delivering contextual and effective Pancasila Education. To preserve national identity amid rapid globalization, Pancasila Education must evolve into a value-based education that adapts to social and digital dynamics.